Designing a Desktop Application for Ship Monitoring and AIS Data Storage Based on RTL-SDR and Raspberry Pi Using Python and PyQt - Muhammad Abiraihan; Rizkayeni Marta; Syukhri; Hadi Kurnia Saputra (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This research aims to develop a desktop application for Monitoring Ships and storing data from the Automatic Identification System (AIS) utilizing Realtek Software Defined Radio (RTL-SDR) and Raspberry Pi devices. The development method employed is the waterfall model, using Python and PyQt as the main programming languages. Black-box testing was conducted on the application, covering aspects such as decoding AIS messages, real-time monitoring, historical data storage, and statistical analysis of the data. The test results indicate that the application successfully addresses challenges faced by the simple AIS receiver, achieving the research objectives by accurately decoding AIS messages, monitoring ship journeys in real-time, storing AIS data as historical data, and presenting informative statistical data. Despite some lag, especially on the Raspberry Pi device, the application contributes positively with improved accuracy and functionality. Further evaluation, technological updates, and integration with other devices are expected to enhance the application's performance. The use of Python and PyQt provides a foundation for further development to enhance the quality of ship navigation systems. It is recommended to involve the decoding of other AIS message types in future research and to consider building a ship journey simulation system for an interactive user experience.